Disease resistance or growth: the role of plant hormones in balancing immune responses and fitness costs - Denancé, Nicolas; Sánchez-Vallet, Andrea; Goffner, Deborah; Molina, Antonio (Frontiers in Plant Science, 2013)
Plant growth and response to environmental cues are largely governed by phytohormones. The plant hormones ethylene, jasmonic acid and salicylic acid (SA) play a central role in the regulation of plant immune responses. In addition, other plant hormones, such as auxins, abscisic acid (ABA), cytokinins, gibberellins and brassinosteroids, that have been thoroughly described to regulate plant development and growth, have recently emerged as key regulators of plant immunity. Plant hormones interact in complex networks to balance the response to developmental and environmental cues and thus limiting defense-associated fitness costs. The molecular mechanisms that govern these hormonal networks are largely unknown. Moreover, hormone signaling pathways are targeted by pathogens and pests to disturb and evade plant defense responses. In this review, we address novel insights on the regulatory roles of the ABA, SA and auxin in plant resistance to pathogens and we describe the complex interactions among their signal transduction pathways. The strategies developed by pathogens to evade hormone-mediated defensive responses are also described. Based on these data we discuss how hormone signaling could be manipulated to improve the resistance of crops to pathogens.